Penerapan Metode Seven Tools Untuk Pengendalian Kualitas Biji Kopi Arabika (Studi Kasus Grand Melati Coffee & Roastery Di Kota Langsa) - Muhammad Husein Muhammad Husein; Meri Andriani; Dewiyana Dewiyana (Jurnal Industri Samudra, 2025)
Grand Melati Coffee & Roastery is one of the coffee shop SMEs in Langsa City that operates in the field of beverages and coffee bean processing. The products produced are coffee drinks and arabica coffee beans that have been marketed both within and outside Langsa City. The quality control implemented at Grand Melati Coffee & Roastery is not very good, as evidenced by the frequent discovery of defective products and the inability to identify the causes of defects in detail. Efforts that can be made to ensure the quality of a product include taking preventive measures against potential failures in the coffee bean production process. The aim of this research is to identify the factors that cause defects in coffee bean products and to analyze the quality control of the coffee bean production process at Grand Melati Coffee & Roastery. The method used in this study is the seven tools method. Based on the research results, The total coffee bean production at Grand Melati Coffee & Roastery during June 2023 was 112 Kg with the amount of defective coffee products being 19.125 Kg. The dominant causes of these defects are human factors, materials, methods, and machines.